KEMAMPUAN GURU PENDIDIKAN AGAMA BUDDHA DALAM IMPLEMENTASI KURIKULUM MERDEKA DI SMK - Metta Budiyanti; Mujiyanto Mujiyanto; Widia Darma (Jurnal Muara Pendidikan, 2023)
The Independent Curriculum is a new curriculum that not all schools have implemented. The implementation of the independent curriculum has changes from the previous curriculum which makes teachers feel difficult. The purpose of this study is to describe the ability of Buddhist Religious Education teachers in preparing Merdeka Curriculum learning tools at SMK Negeri 2 Pengasih, Kulon Progo Regency, and to describe the ability of Buddhist Religious Education teachers in implementing the Independent Curriculum in Buddhist Religious Education learning at SMK Negeri 2 Pengasih, Kulon Progo Regency. This research is a qualitative study with an analytic descriptive approach. Data collection using observation, documentation and interviews. Six informants in this study were selected by purposive sampling. Data analysis used the Cresswel model. The results of the study found that the ability of Buddhist Religious Education teachers in preparing Independent Curriculum learning tools at SMK Negeri 2 Pengasih has fulfilled all components of the Head of the Education Curriculum and Assessment Standards Agency and the Teaching Modules designed are arranged coherently and clearly. The ability of the Buddhist Religious Education teacher in implementing the Independent Curriculum in Buddhist Religious Education Learning at SMK N 2 Pengasih, Kulon Progo Regency is in accordance with the Teaching Module he prepared. Buddhist Religious Education teachers are able to bring the profile of Pancasila students to be interesting by using a scientific approach and carrying out differentiated learning.